Characteristics of specialized single-phase high voltage doubler rectifier - Brzhezytskyi, V.O.; Vendychanskyi, R.V.; Trotsenko, Ye.O.; Haran, Ya.O.; Desyatov, O.M.; Khominich, V.I. (Електротехніка і електромеханіка, 2018)
Introduction. To obtain a high voltage direct current, voltage multipliers with a number of cascades of three or more are widely used. At the same time, for voltage levels of 100…200 kV there are several advantages of using a specialized single-phase high voltage doubler rectifier. Problem. The main difficulty is that at the moment mathematical modeling has not been worked out for describing modes that use the built-in R, C-filter, as well as a nonlinear load in the form of Zener diodes. Goal. Generalization of the results of the authors' previous publications on the development of an analytical method for calculating the modes of a typical high-voltage direct current installation based on a specialized single-phase voltage doubler rectifier. Methodology. Compilation of a system of algebraic linear and nonlinear equations that describe the current and voltage modes in the elements of a typical high-voltage direct current installation with a nonlinear load. Results. It is shown that with the use of linearization of the currentvoltage characteristics of Zener diodes used in the load circuits of a typical high-voltage direct current installation, an analytical solution for the voltages and currents in its elements can be obtained. Originality. The theoretical basis of the complex solution of the system of equations for the currents, voltages and power of the elements of a typical high-voltage direct current installation with the account of nonlinear pulsations is formulated for the first time. Practical value. The obtained theoretical results can be used for calculations, design, optimization of the modes for a wide range of high-voltage direct current installations of technical, technological, and measuring purposes in the range up to 100...200 kV